Crystallisation in polymer nanocomposites - Jog, Jyoti Prakash (Materials Science and Technology, 2006)
Polymer nanocomposites are of interest as they exhibit extraordinary properties compared with the base polymer. The second phase dispersed in the polymer matrix can be carbon nanotubes, semi-conducting inorganic nanoparticles or layer silicates such as clay. Crystallisation in these materials is also of great interest. Polymers exhibit structures at various scales (e.g. lamella, unit cell and spherulites) and the presence of a second phase has a profound effect on crystallisation. General trends observed include acceleration/retardation of crystallisation, changes in spherulite morphology and, in a few cases, changes in the crystal structure. All these observations relate to the presence of a micrometre scale second phase. However, when the dimensions of the second phase are close to the chain dimensions, the effects on crystallisation become particularly interesting. An attempt is made in the present review to address the effect of a nanoscale second phase on aspects such as isothermal and non-isothermal crystallisation, spherulite growth, phase transformation and polymorphism.
Keywords: clay; crystallisation; Nanocomposites; polymer matrix composites

Assessing feasibility of polyarylate-clay nanocomposites towards improvement of gas selectivity - Bhole, Yogesh S.; Wanjale, Santosh D.; Kharul, Ulhas K.; Jog, Jyoti Prakash (Journal of Membrane Science, 2007)
Polymer-clay nanocomposites are well known to reduce the penetrant permeability by following tortuous path. Effects of such reduction in gas permeability on variation in selectivity of nanocomposites prepared using a high permeability polymer were examined. The polyarylate: poly (tetramethyl bisphenolA-iso/terephthalate) that exhibits high permeability and moderate selectivity was chosen for making nanocomposites with two organically modified clays (Cloisite 6A and 10A) by solution intercalation method. The nanocomposite formation for various clay loadings (3, 5 and 7% w/w) in polyarylate was ascertained by change in physical properties (X-ray diffraction, DMA, TEM). Behavior of solution viscosity and nanocomposite density indicated existence of polymer-clay layer interactions. As anticipated, though the gas permeability of pure gases, viz., He, N-2, CH4 and CO2 exhibited decrease, it was not monotonous. This decrease was more for larger gases (N-2, CH4 and CO2) in comparison to the decrease for smaller gas (He) permeability. This led to a decrease in CO2/N-2 and CO2/CH4 selectivities and increase in He/CO2 selectivity; while He/CH4 selectivity was increased substantially at 7% clay loading. This variation indicated feasibility of nanocomposites formation as a tool for improving selectivity of certain gas pairs. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Gas permeation; Nanocomposites; polyarylates; selectivity; solution intercalation

Dielectric relaxations in PVDF/BaTiO3 nanocomposites - Chanmal, Chetan; Jog, Jyoti Prakash (Express Polymer Letters, 2008)
The present work aims at the study of molecular relaxations in PVDF/BaTiO3 nanocomposites using broadband dielectric spectroscopy. The nanocomposites of PVDF with BaTiO3 ( 10-30% by wt%) are prepared using simple melt mixing method. In dielectric permittivity study, two relaxation processes are identified corresponding to the crystalline, glass transition in the PVDF/BaTiO3 nanocomposites. The peaks shift to higher frequencies as the temperature is increased. Electric modulus formalism is used to analyze the dielectric relaxations to overcome the conductivity effects at low frequencies. In M `' spectra two peaks are observed only at high temperature and low frequency whereas a single relaxation peak appears at low temperatures. The single relaxation peak appearing at low temperatures is the alpha(c) relaxation attributed to crystalline chain relaxation in PVDF and the second relaxation peak which appears only at high temperatures and at a frequency lower than alpha(c) relaxation is identified as MWS relaxation. The temperature dependence of alpha(c) relaxation and MWS relaxation follows Arrhenius type behavior.
Keywords: dielectric spectroscopy; Interfacial polarization; MWS relaxation; Nanocomposites

Molecular dynamics of copolyester/clay nanocomposites as investigated by viscoelastic and dielectric analysis - Kalgaonkar, Rajendra A.; Jog, Jyoti Prakash (Journal of Polymer Science Part B-Polymer Physics, 2008)
We have investigated the molecular dynamics of poly(ethylene glycol-co-cycloxeane-1,4-dimethanol terephthalate) (PETG) nanocomposites based on a organically modified layered silicate. Intercalated namocomposites were prepared by melt compounding technique as evidenced from the X-ray diffraction and transmission electron microscopy studies. Two relaxation processes were observed in pure PETG as well as in the nanocomposites. The low-temperature beta-process was assigned to the local motions of C=O polar groups and the alpha-process was due to the glass-rubber transition or the segmental relaxations associated with the polymer chain backbone. Presence of layered silicates accelerated alpha-relaxation dynamics in the nanocomposites accompanied by a depression in T(g) which was attributed to the reduced intermolecular cooperativity between intercalated polymers chains. Additionally, a direct comparison between the viscoelastic and dielectric studies shows excellent agreement between the accelerated alpha dynamics of the nanocomposites. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2539-2555, 2008
Keywords: clay; Dielectric relaxation; Nanocomposites; polyesters